Revolution of CRISPR Technologies: Applications, Limitations, and Implications for the Future of Gene Therapy in Indonesia - Endeh Apriyanti; Ahsanal Kasasiah; Aliya Azkia Zahra; Aliza Salsabila Ainaputri; Cantika Aprillia; Dewi Pratiwi Purba Siboro (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Gene editing has emerged as a transformative approach in biomedical science, enabling precise modification of genomic sequences to investigate gene function and develop novel therapeutic strategies. Among available technologies, CRISPR-Cas9 has revolutionized genome engineering due to its simplicity, programmability, high efficiency, and cost-effectiveness. This review examines the mechanisms, biomedical applications, limitations, ethical considerations, and future prospects of CRISPR technology, with particular emphasis on its relevance to gene therapy in Indonesia. CRISPR has demonstrated significant potential in treating monogenic disorders such as β-thalassemia and sickle cell disease, advancing cancer research through gene targeting and immunotherapy, and enabling innovative antiviral strategies and molecular diagnostics. These applications highlight its potential to provide precise and potentially curative therapies. However, several challenges remain, including off-target effects, limitations in delivery systems, biological complexity, and uncertainties regarding long-term safety. Ethical concerns, particularly related to germline editing, informed consent, and social equity, further complicate its clinical application. In Indonesia, CRISPR development is still at an early stage, with applications largely limited to research settings. Key challenges include limited infrastructure, insufficient expertise, evolving regulatory frameworks, and low public awareness. In conclusion, CRISPR holds strong potential for advancing gene therapy in Indonesia, but its successful implementation requires strengthened regulation, improved infrastructure, capacity building, and greater public engagement to ensure safe and ethical use.